2013
DOI: 10.1179/1362171812y.0000000100
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat affected zone softening in armour steels Part 1 – Phase transformation kinetics

Abstract: Heat affected zone (HAZ) softening in two armour steels (high hard and flash processed) was investigated by monitoring phase transformations during simulated welding thermal cycles. The high hard steel was produced by conventional thermomechanical processing followed by quench and tempering. Flash processed steel was produced by rapid heating and cooling of a spheroidised steel to produce a mixed microstructure. Heat affected zone softening in high hard steel was observed on heating to a peak temperature below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In another example, the role of initial microstructure (e.g., distribution of carbides and chemical segregation) in advanced high-strength steels (AHSS) and its response to welding was attributed to improved ballistic properties in comparison to welds made with homoge-neous materials (Refs. 35,36). Similarly, during spot welding a small change in the electrode curvature led to large changes in weld nugget development - Fig.…”
Section: Description Of Geometry Material and Processing Boundary Cmentioning
confidence: 92%
“…In another example, the role of initial microstructure (e.g., distribution of carbides and chemical segregation) in advanced high-strength steels (AHSS) and its response to welding was attributed to improved ballistic properties in comparison to welds made with homoge-neous materials (Refs. 35,36). Similarly, during spot welding a small change in the electrode curvature led to large changes in weld nugget development - Fig.…”
Section: Description Of Geometry Material and Processing Boundary Cmentioning
confidence: 92%
“…The heat affected zone (HAZ) exhibits softening due to tempering [1,10]. This softened zone often exhibits low creep and fatigue properties and poor ballistic performance [11,12] compromising the integrity of the structure. Additionally, like most high strength low alloy steels, Q&T steels are susceptible to hydrogen-assisted cold cracking.…”
Section: Introductionmentioning
confidence: 99%
“…This classification distinguishes steels that have the isotropic mechanical and ballistic properties in the rolling direction and steels with anisotropy properties. The most commonly used steels are cast homogeneous armor (CHA), rolled homogeneous armor (RHA), high-hardness armor (HHA), dual hardness armor (DHA) and hardened face armor (HFA) [1]. Modenesi et al [2] showed a summary of the formation of heataffected zone (HAZ) in different base materials in welded joints, with variations in the thermal cycle, with four basic groups being solid hardened alloys, hardened alloys, precipitation hardened alloys and transformable alloys, each one forming different divisions in the microstructure of the HAZ.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the heat involved in welding processes changes their structure significantly, especially those that require high values of welding energy. The main problems occurring in steels with carbon percentages above 0.25% C is that of no tempered martensitic is formed with high hardness in the heat-affected zone (HAZ), nevertheless, with a great brittleness, as occurred in the HHA steel [1]. Indeed, microstructure is one of the most important factors to analyze in the HHA steel because changes in mechanical properties such as toughness, ductility and hardness directly affect the ballistic properties such as drilling resistance, spalling and fragmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation